A educação do paulista pela imprensa: uma análise do jornal A Notícia na Revolução Constitucionalista de 1932 (São José do Rio Preto/SP) - Silva, Victor Henrique Diana da (2022)
This research focuses on the history and the memory of the 1932 Constitutionalist Revolution, which took place in São José do Rio Preto-SP, built by means of the city's periodic press. To this end, the newspaper A Noticia, the most influential local press, was used as a source, in a chronological period that encompasses the period from 1932 to 1980. This is justified because of the year of the outbreak of the revolution (1932) and the end of the period that the periodical's director, Leonardo Gomes, was at thente of the press (late 1960s). The reading of the newspaper extended over these years because it was assumed that the newspaper played an important role in mobilizing people, as well as in building memory about the revolution. In the light of the social history of the press (BURKE, 2005; LUCA, 2008) and of the research on memory (NORA, 1993; HALBWACHS, 1990; LE GOFF, 1996), we seek to problematize the educational role of such press in the construction of ideal citizens identified with the so-called "causa paulista". Supposedly haughty and educated subjects that, in the period, should take up arms aiming to defend the Paulista way of life, seen as an ideal to be followed by the rest of the country.